Safeguarding Ayrshire’s Coalmining Past: Heritage, Nostalgia and Social Memory - Laurence Gourievidis (Revue LISA)
Scotland’s industrial past is central to its national narrative, and heritage discourse has long focused on engineering and technical achievements. However, this article considers another facet of industrial heritage, one which is local, engages with deindustrialisation and, initiated from the grassroots, projects the vision of working-class communities. Focusing on the example of the Barony colliery in East Ayrshire, a former deep mine in the south west of Scotland, it explores the initiative undertaken by a local volunteer group to restore and interpret the site. This article argues that, whilst this project brings to light the multi-functional uses of heritage as a resource, it also underlines the crucial function of social memory in heritage work, particularly in districts with high levels of socio-economic deprivation twinned with a degraded self-image. Against a problematic present and future, the fostering of a sense of past and place, tinted with nostalgia, yet confronting painful and uncomfortable aspects of the past with their long-term consequences, serves healing and regenerative purposes, instilling a sense of pride and dignity in communities, and ultimately striving to shore up their self-esteem.